PREVALENCE OF ORAL CANDIDIASIS AMONG CANCER PATIENTS ATTENDING A TERTIARY CARE HOSPITAL IN RANCHI, EAST INDIA: A RETROSPECTIVE STUDY. - Seema, Kumari; Kumar, Abhay; Ashok Kumar Sharma; Manju , Boipai; Kumar, Manoj (Student's Journal of Health Research Africa, 2023)
Background: Within the past two decades, Candida species have emerged as major human pathogens and are currently the fourth most common cause of nosocomial infection. Propose of this study was to determine the occurrence of oral Candidiasis among cancer patients at Rajendra Institute of Medical Sciences, Ranchi. Materials and Methods: Sixty cancer patients were examined for oral candidiasis. For all patients, the clinical diagnosis had to be confirmed microbiologically by the presence of yeasts and/or hyphae or pseudohyphae on potassium hydroxide– treated smears of oral swabs. Oral samples were obtained and cultured on Sabouraud's dextrose agar and CHROMagar. Results: 25 out of the 60 patients (41.7%) were males and 35 (58.3%) were females ranging in age from 15 to 79 years. Gastrointestinal cancer and Breast cancer were the most frequent cancer in the studied group, accounting for 65 % and 18.4 % respectively. The mean weight of the patients was 52.67 Kg (range, 38– 80 Kg). Similarly, the mean of hospital stay was 3.58 days (range; 1-9 days). From these patients, 19 Candida spp were isolated; C. albicans alone outnumbered other species and accounted for 73.68% of episodes of trash. For C. albicans isolates, the MIC values range from 1 to 9 µ g / ml µg / ml for polyenes and from 0.03 to 16 µ g / ml for the azole antifungals. All the Candida albicans had closely related MFCs values. Conclusion: In conclusion, the finding of our study strongly suggests that oral candidiasis is a frequent complication among cancer patients, being C. albicans as the main etiological agent.